Intrinsic and extrinsic goals as moderators of stress and depressive symptoms in Chinese undergraduate students: A multi-wave longitudinal study. Issue 1 (December 2016) - Ling, Yu; He, Yushu; Wei, Yong; Cen, Weihong; Zhou, Qi; Zhong, Mingtian
Abstract Background Studies in western countries have examined the specific vulnerability hypothesis of Dykman's theory of goal-orientation predispositions to depression through two-time point designs. The purpose of this prospective longitudinal study was to investigate the moderating effects of intrinsic and extrinsic goals on stress and depressive symptoms in Chinese undergraduate students. Methods A total of 462 undergraduate students [46 % female; mean age, 19.06 (range, 17–22) years] completed self-reported measures assessing intrinsic and extrinsic goals, depressive symptoms, and the occurrence of social and academic hassles. Every 3 months over the subsequent 12 months, the undergraduate students completed measures assessing depressive symptoms and the occurrence of daily hassles. Results Results of hierarchical linear modeling analyses indicated that undergraduate students with low levels of intrinsic goals reported greater depressive symptoms following the occurrence of social and academic hassles than did those with high levels of such goals. However, undergraduate students with high levels of extrinsic goals did not report greater depressive symptoms following the occurrence of social and academic hassles than did those possessing low levels. Conclusions These findings suggest that intrinsic goals can protect undergraduate students experiencing high levels of social and academic hassles from depressive symptoms. The study findings provide new insight into the course of depressive symptoms among undergraduate students, and offer psychologist and psychiatrists ways to protect individuals from depressive symptoms by building up intrinsic goals.